Manajemen Risiko pada Lembaga Keuangan Syariah di Era Digital - Jailani, Novalini (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2024)
This article aims to explain risk management in Islamic financial institutions in the digital era. This research uses a qualitative approach in the form of literature studies, namely by collecting information or data from various books, articles, journals, and reports relevant to the research. The results show that advances in information technology in the digital era require Islamic Financial Institutions to improve operational efficiency, accuracy, speed of service, and security. On the other hand, Islamic Financial Institutions is faced with information technology, operational, and reputational risks that require effective security strategies and an understanding of the latest threat trends in the digital era. Effective risk management is important for Islamic Financial Institutions in facing the challenges of the digital era, with the aim of providing a better understanding of risk management in the context of Islamic financial institutions.